The Compatibility between Teaching Methods and Competence-Based Curriculum in Tanzania - Tilya, F.; Mafumiko, F. (Papers in Education and Development, 2018)
This paper discusses the classroom problems of implementing the competence-based, learner-centred curriculum. The paper first describes the confusion with respect to teaching methods inTanzania. Then it links the confusion with the recently introduced competence-based curriculum. The paper elaborates on the problems facing the teacher in implementing the curriculum that requires learner-centred teaching approaches. The paper ends with some reflections which put forward some recommendations.